Students Attitude Complexities in Gender Equality: Examining its Perception - Tenedero, Cynic J.; Enguito, Geraldine; Ferrer, Marielle Kharla; Juan, Elizabeth San; Villacer, Hazel; Sicuan, Syrenzo R. (Universitas Muhammadiyah Mataram, 2024)
The importance of addressing gender equality in education lies in its critical role in fostering inclusivity, diversity, and equitable opportunities for all learners. This study explored students' attitudes toward gender equality, focusing on their perceptions in academic, personal, and extracurricular contexts, to better understand prevailing attitudes and identify areas requiring attention. Employing a quantitative research design, data were collected from 45 students enrolled in the Bachelor of Science in Food Technology program at the Technological University of the Philippines through a validated survey. ANOVA was utilized to analyze whether significant differences existed in gender equality perceptions across respondent groups. This technique was chosen for its relevance in assessing variance within and between groups, providing insights into attitudinal uniformity or diversity among students. Results showed overwhelmingly positive attitudes toward gender equality, with strong agreement that gender should not limit participation or performance in academic and extracurricular settings. However, slight gaps were observed in areas such as institutional support for extracurricular activities and equitable treatment of genders within familial environments. The ANOVA findings revealed no statistically significant differences among groups, underscoring the uniformity in perceptions despite diverse backgrounds. These findings highlight the progress made in promoting gender equality while emphasizing the need for continuous efforts to address unconscious biases and support inclusivity in education. The study contributes to the growing discourse on gender equality in educational contexts and serves as a call to action for institutions to prioritize inclusive practices across all facets of student life.